Occurrence of Incisional Complications After Closure of Equine Celiotomies With USP 7 Polydioxanone. Issue 4 (17th September 2014) - Anderson, Stacy L.; Devick, Ian; Bracamonte, Jose L.; Hendrick, Steve; Barber, Spencer M.; Carmalt, James L.; Wilson, David G.
<x xml:space="preserve">Abstract</x> Objectives To report the occurrence of, and risk factors associated with, incisional complications of equine ventral median celiotomies closed with USP 7 polydioxanone (7PD). Study Design Retrospective case series. Sample Population Horses (n = 73; 75 celiotomies). Methods Medical records (2000–2010) were retrieved and reviewed for horses that had a ventral celiotomy closed with 7PD and survived ≥14 days. Follow‐up (>1 year) was obtained from the medical record, owner, or referring veterinarian. Independent variables were selected based on risk factors identified in previous studies, perceived clinical relevance, and if there were adequate data recorded in the medical record. Statistical analysis, including multivariable logistic regression with a forward‐building model process, was performed to evaluate variables associated with incisional complications. Results One or more incisional complication(s) occurred in 19 celiotomies (25.3%) during hospitalization or after discharge including: drainage (25.3%), infection (12.0%), and partial dehiscence (5.3%). Two of 63 horses (3.2%) available for follow‐up developed an incisional hernia. Variables associated with incisional complications after multivariate analysis included: number of days hospitalized, surgery time, postoperative colic, and postoperative fever. Conclusion Overall occurrence of incisional herniation after closure of ventral celiotomies with 7PD was low.